189k views
3 votes
Find y as a function of x if
x^(2) y''-4xy'-6y= x^(3)
y(1)=6 and y'(1)=-1

User Samufi
by
6.3k points

1 Answer

3 votes
Let
y(x)=z(t), where
t=\ln x. Then


\implies y'=\frac1xz'

\implies y''=\frac1{x^2}(z''-z')

so the ODE is equivalent to


(z''-z')-4z'-6z=e^(3t)

z''-5z'-6z=e^(3t)

The characteristic equation is


r^2-5r-6=(r-6)(r+1)=0\implies r=6,r=-1

so that the characteristic solution is


z_c=C_1e^(6t)+C_2e^(-t)

For the particular solution, take


z_p=ae^(3t)

\implies {z_p}'=3ae^(3t)

\implies {z_p}''=9ae^(3t)


\implies 9ae^(3t)-15ae^(3t)-6ae^(3t)=e^(3t)

\implies -12a=1

\implies a=-\frac1{12}


\implies z_p=-\frac1{12}e^(3t)


\implies y_p=-\frac1{12}x^3


\implies y=y_c+y_p=C_1x^6+\frac{C_2}x-\frac1{12}x^3

With the initial conditions, we get


y(1)=6\implies 6=C_1+C_2-\frac1{12}

y'(1)=-1\implies -1=6C_1-C_2-\frac14

\implies C_1=(16)/(21),C_2=(149)/(28)

So the particular solution to the IVP is


y=(16x^6)/(21)+(149)/(28x)-(x^3)/(12)
User Sarwan Kumar
by
6.9k points